2018
DOI: 10.1111/hsc.12547
|View full text |Cite
|
Sign up to set email alerts
|

“Something that happens at home and stays at home”: An exploration of the lived experience of young carers in Western Australia

Abstract: There are approximately 350,000 young carers in Australia, yet their experience is not well understood. Young carers face adversities and disenfranchisement by being a young person in a caring role, and the role can affect other areas of their lives. We explored the lived experiences of young carers, aged 14-25 years (N = 13), from Western Australia through in-depth semi-structured interviews. A phenomenological approach was adopted. A thematic analysis of the transcribed interview data revealed four key theme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 35 publications
4
35
0
Order By: Relevance
“…The few previous quantitative studies with measures of both positive and negative outcomes have indicated that children experience caregiving as more positive than negative (Joseph et al, 2009;Mechling, 2015;Pakenham et al, 2007;Shifren et al, 2014), which seems in line with qualitative studies showing that children overall experience the caregiving as positive (Heyman & Heyman, 2013;McDougall, O'Connor, & Howell, 2018;Nicholls, Patterson, McDonald, & Hulbert-Williams, 2016). If we further explore why some children experience caregiving as positive while others experience more negative outcomes, we may possibly be able to better identify children affected by parental illness and as young carers in need of interventions developed.…”
Section: Outcomes Of Children's Caregiving Across Different Types Of supporting
confidence: 58%
“…The few previous quantitative studies with measures of both positive and negative outcomes have indicated that children experience caregiving as more positive than negative (Joseph et al, 2009;Mechling, 2015;Pakenham et al, 2007;Shifren et al, 2014), which seems in line with qualitative studies showing that children overall experience the caregiving as positive (Heyman & Heyman, 2013;McDougall, O'Connor, & Howell, 2018;Nicholls, Patterson, McDonald, & Hulbert-Williams, 2016). If we further explore why some children experience caregiving as positive while others experience more negative outcomes, we may possibly be able to better identify children affected by parental illness and as young carers in need of interventions developed.…”
Section: Outcomes Of Children's Caregiving Across Different Types Of supporting
confidence: 58%
“…Authors 1, 2, 6, 8, 9, and 15 regularly discussed emerging themes and examples; any disagreements were resolved by consensus discussion, as per usual practice. 43,44 Quality Authors 1 and 2 led the analysis of the transcripts; the other authors contributed to interpretation. Nine coding categories were identified and from these, two over-arching themes and three sub-themes emerged (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…If these resources are available and adaptational systems function normally, resilience to developmental threats is expected to be common rather than exceptional or rare (Masten & Obradović, 2006). Nevertheless, much of the research on young carers to date has focused on elucidating the unique experiences and especially the characteristic challenges these young people face (McDougall et al, 2018;Metzing & Schnepp, 2008;Nigel et al, 2003).…”
Section: Resilience As a Guiding Concept For Studying Adaptation Inmentioning
confidence: 99%